Empresa Distribuidora del Pacifico S. A. E.S.P. : implementación del plan de reducción de pérdidas de energía (2017)
"The Electrificadora del Chocó faced an economic crisis in the middle of 2000 that motivated the Colombian Government to carry out the intervention and later liquidation of this company. The same year, on July 29th, DISPAC acquired the assets of the Electrificadora and started activities in that department designing and implementing a management model for the provision of the service, demonstrating the improvement of operational indicators, mainly energy losses... In accordance with the above, the objective of this degree work was to analyze the relevance and effectiveness of the decisions taken in the Plan, located prior to the presentation of the Plan ending the 2015, applying the concepts and tools of the management to respond to whether the decisions made by Empresa Distribuidora del Pacifico S.A. E.S.P., were adequate and effective, from the financial outlook, for the implementation of the 2016-2017 energy loss reduction plan." -- Tomado del Formato de Documento de Grado.